Endoscopic management of gastric ectopic pancreas with repeated ulcerations and bleeding: A case report - Tomoya Kimura; Yohei Minato; Susumu Banjoya; Toshifumi Iida; Koichi Furuta; Shinya Nagae; Yohei Ito; Hiroshi Yamazaki; Nao Takeuchi; Shunya Takayanagi; Yoshiaki Kimoto; Yuki Kano; et al. (DEN Open)
Abstract A 25‐year‐old man was referred to our center for investigation of a gastric submucosal tumor and an ulcer that had developed on its oral side. Endoscopic ultrasonography findings suggested the presence of an ectopic pancreas, and treatment with an oral proton pump inhibitor was planned for the ulcer. Over the subsequent 3 years, the patient endured recurring epigastric pain and episodes of passing black stools. Emergency endoscopy revealed that the morphology of the gastric submucosal tumor had transformed into a pedunculated polyp‐like morphology with a bleeding ulcer at the apex of the lesion. Endoscopic hemostasis using hemostatic forceps was performed. However, the patient continued to pass black stools. In light of the persistent symptoms and unique morphology of the lesion, endoscopic resection was attempted as a curative approach. The lesion was excised by hot snare polypectomy. Post‐treatment, the patient exhibited no signs of recurrence, marking a successful resolution. Three months later, a gastroduodenal endoscopy showed that the excised site had undergone scar formation without recurrence of the lesion. This case holds significant clinical value as it demonstrates the efficacy of a minimally invasive treatment strategy in managing repeated bleeding ulcerations of an ectopic pancreas, ultimately achieving a complete cure.